The SAGE handbook of qualitative research - Denzin, Norman K.; Lincoln, Yvonna S. (SAGE Publications, Inc., 2018)
The substantially updated and revised Fifth Edition of this landmark handbook presents the state-of-the-art theory and practice of qualitative inquiry. Representing top scholars from around the world, the editors and contributors continue the tradition of synthesizing existing literature, defining the present, and shaping the future of qualitative research. The Fifth Edition contains 19 new chapters, with 16 revised making it virtually a new volume while retaining six classic chapters from previous editions.